Construction of Ideology in Teacher Protection Regulation: A Systemic Functional Linguistic Approach - Rohmatunnazilah, Rohmatunnazilah (Allure Journal, 2025)
This study explores how teacher protection regulations in Indonesia are discursively shaped by ideological structures embedded within legal language. Employing the framework of Systemic Functional Linguistics (SFL), particularly the transitivity system, this study analyses selected clauses from three regulatory documents Law No. 14/2005, Government Regulation No. 74/2008, and Ministerial Regulation No. 10/2017 focusing on how participants, processes, and agency are represented. Transitivity patterns were examined to identify grammatical structures, which were then interpreted using van Dijk’s socio-cognitive approach to uncover ideological meanings. The findings reveal a consistent use of material, relational, and verbal processes that portray the state as an active and authoritative agent, while teachers are positioned primarily as passive participants. In addition, the pervasive use of nominalization obscures agency and reframes social actions as depersonalized, technocratic procedures. These linguistic patterns are indicative of a broader neoliberal ideological framework, characterized by symbolic legalism, bureaucratic formalism, and the suppression of individual agency. Rather than enabling empowerment, the discourse of protection constructs a hierarchical relationship in which the state centralizes authority and reduces teacher agency. This study contributes to the critical examination of education policy by highlighting how regulatory discourse reproduces institutional dominance and calls for a more participatory, justice-oriented approach to teacher protection.